OP0140-HPR Preliminary Results of A Randomized Clinical TRIAL Comparing the Effectiveness of A Non-Pharmacological Multidisciplinary Group-Based Treatment Program with A Telephone Monitored Program on Daily Function in Patients with Generalized Osteoarthritis. (10th June 2014) - Cuperus, N.; Hoogeboom, T.; Kersten, C.; Rietveld, L.; den Broeder, A.; Vliet Vlieland, T.; van den Ende, C.
Abstract : Background: It has been suggested that individuals with generalized osteoarthritis (GOA) represent a large subgroup of patients with OA 1 . However, the effectiveness of a non-pharmacological intervention in the management of GOA is unknown as research has mainly focused on a specific localization of OA (e.g. hip, knees or hands). In addition, there is lack of evidence concerning the optimal treatment intensity and mode of treatment delivery. Objectives: To compare the effectiveness of a non-pharmacological fully supervised group-based multidisciplinary treatment program with a telephone monitored treatment program for patients with GOA on daily function six weeks and six months after treatment 2 . Methods: In this parallel group, single blind randomized clinical trial, individuals with a clinical diagnosis of GOA were randomly allocated to either a six week fully supervised multidisciplinary group-based treatment program or a six week telephone monitored treatment program. Both programs aimed to improve daily function and to enhance self-efficacy to control the disease. The programs had comparable content but differed in mode of delivery and intensity. Primary outcome (daily function measured with the Health Assessment Questionnaire Disability Index (HAQ-DI)) and secondary outcome measures were assessed at six weeks and six months. Differences in mean change scores between both treatment groups were analysed using analysis of covariance (ANCOVA) adjusting for baseline levels. T-test statistics were performed to assess changes within groups. Results: Of 158 randomized patients (mean (SD) age 60 (8); female 85%), 147 (93%), 137 (87%) and 132 (84%) patients completed the baseline, six weeks and six months follow-up measurements respectively. No difference in effectiveness between both treatment groups was found on the HAQ-DI. Statistical significant differences between both groups were found in favour of the group-based intervention for pain after six weeks (adjusted mean difference (95%CI): -1.77 (-3.49 - -0.07), p=0.04). However, no differences between groups on other secondary outcomes were found. In both groups, there was no significant improvement (p>0.05) in daily function after treatment measured with the HAQ-DI, whereas significant improvements on the Patient Specific Functioning Scale (PSFS) were shown after six weeks (4 points (on a scale ranging from 0-100) for both treatment programs) and after six months (5 points for the telephone monitored program; 11 points for the group-based intervention). In addition, the group-based intervention showed significant improvements (p<0.05) for pain and fatigue. Conclusions: In this trial we found no differences in effect between two modes of delivery of non-pharmacological treatment for patients with GOA, except for pain. Therefore, our results imply that the choice of mode of treatment delivery i.e. fully supervised versus telephone monitored could be based on patients' preferences and/or costs. References: Nelson et al. (2013). Seminars in Arthritis and Rheumatism (in press) Hoogeboom et al. (2010). BMC Musculoskeletal Disorders;11:142 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3507